Econometric models of monetary policy effectiveness in Ukraine - Baranovskyi, O. I.; Kuzheliev, M. O.; Zherlitsyn, D. M.; Sokyrko, O. S.; Nechyporenko, A. V.; Жерліцин, Д. М. (ТОВ «ФІНТЕХАЛЬЯНС», 2019)
The main task forthe Central Bank is ensuringthe stability of the national currency. For this purpose, it tends to use traditional monetary regulation instruments. There are interest rates regulation, currencies intervention, administrative restriction, money supply adjustmentand so on. A significant number of these traditional tools are effective. However, it is very difficult to assess the effectiveness of the regulators influence.Therefore, the purpose of the work is to define the theoretical substantiation of the basic monetaryregulationinstruments effectiveness and estimate itsinfluence onthe economy growth indicatorsin Ukraine.This article is based on the theoretical principles and methods of macroeconomic analysis; the system approach methods to define the main monetary regulation instruments offinance system and economy. The study presents a regression models with pairedandmultiple variables. For these models R-Studio instruments are the main tools of quality estimation and results interpretation.The article shows the results of statistical analysis of national currency rate and consumer price indexwhichis based on open data of Ukraine economy trends for the period from 2007till2019.Traditionallyeconometric methods are used to find out long run relationships betweenbasic economyindicators (agriculture and industryoutputs, average salary, stock indexgrowth etc.) and both monetary informationandregulation instruments.Authors developthe regressive modelsof influence of Central Bank regulation instruments ofmonetary and economic stability.The paper presents conclusions regarding trends and problems in the implementation of Ukraine’s monetary policy, it’sinfluenceson the currency stability and economic growth trends.Implementation of the proposed measureswill increase monetary policy effectiveness and define the directions of the further research in forecasting inflationary and course-forming factors of the development of the national economy and financial system of Ukraine. Thekey focus of further research is to define an adequate indicator that determines the real level of inflation, which must evaluate a whole range of factors reducing the real value of money.

Головним завданням центрального банку є забезпечення стабільності національної валюти. Для цьоговін прагне використовувати традиційні інструменти монетарного регулювання, а саме: регулювання процентних ставок, інтервенції валют, адміністративні обмеження, регулювання грошової маси тощо. Значна кількість цих традиційних інструментів є ефективними. Однак дуже важко оцінити ефективність впливу цих регуляторів.Тому метою роботи є теоретичне обґрунтування ефективності основних інструментів монетарного регулювання та оцінка їхньоговпливу на показники економічного зростання в Україні.Ця стаття базується на теоретичних засадах та методах макроекономічного аналізу; методах системного підходу для визначення основних інструментів монетарного регулювання фінансової системи та економіки. У роботі представлені регресійні моделі з парними та множинними змінними. Інструменти R-Studio є основними для оцінки якості та інтерпретації результатів для цих моделей.Наведенорезультати статистичного аналізу індексів курсу національної валюти та споживчих цін, які базуються на відкритих даних щодо тенденцій розвитку економіки України за період з 2007рокудо 2019-го. Традиційні економетричні методи використовуються для виявлення довготривалих взаємозв’язків між основними економічними показниками (випуски у сільському господарстві та промисловості, середня заробітна плата, зростання фондових індексів тощо), монетарною інформацією та інструментамирегулювання.Складенорегресивну модель впливу інструментів регулювання ЦБ на монетарну та економічну стабільність.Наведеновисновки щодо тенденцій та проблем реалізації грошово-кредитної політики України, її вплив на стабільність валюти та тенденції економічного зростання.Реалізація запропонованих заходів підвищить ефективність грошово-кредитної політики та визначить напрями подальших досліджень у прогнозуванні інфляційних та курсоутворювальнихфакторів розвитку національної економіки та фінансової системи України.Основним напрямом подальших досліджень є визначення адекватного показника, що визначаєреальний рівень інфляції, який повинен оцінювати цілий ряд факторів, що знижують реальну вартість грошей.
Економетричні моделі ефективності монетарної політики в Україні
Keywords: monetary policy; regulation instrument; econometric model; multiple regression; economic indicator; монетарна політика; інструменти регулювання; економетрична модель; множинна регресія; економічний індикатор